Active conductive head cooling of normal and infarcted brain: A magnetic resonance spectroscopy imaging study. Issue 11 (November 2022) - Diprose, William K; Morgan, Catherine A; Wang, Michael TM; Diprose, James P; Lin, Joanne C; Sheriff, Sulaiman; Campbell, Doug; Barber, P Alan
Active conductive head cooling is a simple and non-invasive intervention that may slow infarct growth in ischemic stroke. We investigated the effect of active conductive head cooling on brain temperature using whole brain echo-planar spectroscopic imaging. A cooling cap (WElkins Temperature Regulation System, 2nd Gen) was used to administer cooling for 80 minutes to healthy volunteers and chronic stroke patients. Whole brain echo-planar spectroscopic imaging scans were obtained before and after cooling. Brain temperature was estimated using the Metabolite Imaging and Data Analysis System software package, which allows voxel-level temperature calculations using the chemical shift difference between metabolite (N-acetylaspartate, creatine, choline) and water resonances. Eleven participants (six healthy volunteers, five post-stroke) underwent 80 ± 5 minutes of cooling. The average temperature of the coolant was 1.3 ± 0.5°C below zero. Significant reductions in brain temperature (ΔT = –0.9 ± 0.7°C, P = 0.002), and to a lesser extent, rectal temperature (ΔT = –0.3 ± 0.1°C, P = 0.03) were observed. Exploratory analysis showed that the occipital lobes had the greatest reduction in temperature (ΔT = –1.5 ± 1.2°C, P = 0.002). Regions of infarction had similar temperature reductions to the contralateral normal brain. Future research could investigate the feasibility of head cooling as a potential neuroprotective strategy in patients being considered for acute stroke therapies.